PREVALENSI DAN INTENSITAS INFEKSI Ascaris lumbricoides DAN Trichuris trichiura PADA ANGGOTA KELUARGA DI JAKARTA DAN CIPANAS, JAWA BARAT - Rizal Subahar; Patra Patiah; Widiastuti Widiastuti; Agus Aulung; Heri Wibowo (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2017)
The infection of Ascaris lumbricoides and Trichiuris trichiura may be occured among family members. The aim ofthe study was to know the prevalence and intensity of A.lumbricoidesand T.trichiurainfections among family members in Jakarta and Cipanas, West Java. This study was conducted in two Government Schools, namely SDN Kalibaru 07 Pagi(North Jakarta) and SDN Tarigu(Cipanas, West Jawa) using a cross-sectional design. The feces samples of respondents consisted of father, mother, schoolchildren, as well as other family members. The feces samples were tested by Kato-Katz method. A total of feces samples examined was 842 samples consisting of 242 samples from Kalibaru and 600 from Cipanas. The feces samples were examined by Kato-Katz method. In Kalibaru the prevalences of A. lumbricoides and T.trichiura in father were 27,8% and 13,9%, mother 32,6% and 7,0%, schoolchildren 37,5% and 36,5%, and other family members 30,5% and 21,1% respectively. Statistically, no significant differentiation (p>0.05) of the prevalences of the intestinal helminths among faher, mother, schoolchildren, and other familiy members in Kalibaru. In Cipanas, the prevalences of A. lumbricoides andT.trichiura in fahter were 0,0% and 4,0%, mother 2,0% and 4,70%, schoolchildren 2,0% and 16,7%, and other family members 0,0% and 4,7%. The intensity of A. lumbricoides and T. trichiura infections among the family members in Kalibaru and Cipanans was light to moderate. The A. lumbricoides high infection was only found among schoolchildren in Kalibaru. The family members infected by A. lumbricoides and T. trichiura were a source of infection for transmitting the intestinal helminths in the community.